Impact of current-induced degradation process on the electro-optical characteristics of InGaN/GaN multiple-quantum-well photodetectors fabricated on sapphire substrate - Dalapati, Pradip; Yamamoto, Kosuke; Egawa, Takashi; Miyoshi, Makoto (Applied Physics Letters, 2021)
The impact of defects on the degradation behaviors of InGaN/GaN multiple-quantum-well photodetectors submitted to dc current stress has been intensively studied. The root mechanism for degradation has been studied employing combined electro-optical measurements. The collected results indicate that (i) stress can induce an increase in parasitic current leakage paths and trap-assisted tunneling in reverse and subturn-on forward bias ranges, respectively; (ii) during stress, the overall capacitance increases and localization improves in the apparent carrier concentration within the active region; (iii) stress causes a significant decrease in quantum well intensity and an increase in yellow luminescence; (iv) stress induces an increase in the external quantum efficiency due to broadening of the space-charge region; and (v) the detectivity of the device decreases after the stress treatment. These results suggest that degradation is largely attributed to the activation of initially inactive defects, mainly Mg–H, C-related, and VGa defects in the investigated devices, with consequent worsening of their performances.